Quality of health websites and their influence on perceived usefulness, trust and intention to use: An analysis from Thailand - Sakun Boon-itt (Journal of Innovation and Entrepreneurship, 2019)
People are seeking ways to retrieve information on their health in an innovative way by looking online for information to decide whether or not to visit a doctor. Searching for health information on the Internet is always easy and convenient. However, the evaluation of the quality of health websites is the main issue since the literature on this topic is not as robust as we would like to see. The purpose of this study is to examine health websites' characteristics, which can reveal website quality. In addition, this study also aims to examine the perceived usefulness of health websites based on the information acceptance model. An online survey was conducted to collect data from consumers who used the Internet for information-seeking, with a total of 222 returned responses. The results indicate that health website quality influences the intention to use the health website when users have trust in and perceive the usefulness of the system.
Keywords: 650; Website quality; Health information; Survey